Preparation method of dechlorination ion exchange resin

By preparing a chlorine-removing ion exchange resin containing modified lignin and plasma treatment, the problem of difficulty in removing chlorine ions in water in the existing technology is solved, and an efficient, stable and long-life chlorine removal effect is achieved.

CN119346188APending Publication Date: 2025-01-24YIDING SHANGHAI INFORMATION TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411777104.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove chloride ions in water, resulting in soil salinization and human health risks.

Method used

The preparation method of exchanging resin exchanging resin in chloride ions is used to react through materials such as styrene, modified lignin, and puppet nitrogen dose, and form a resin with high chloride performance. Improve the affinity of resin, and eventually improve the efficiency of chloride dehuminating through plasma treatment.

Benefits of technology

It achieves efficient removal of chlorine ions in water, improves the chlorine removal efficiency and selectivity of the resin, extends the service life of the resin, and reduces the invasion of pollutants.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to dechlorination ion exchange resin and a preparation method thereof, and belongs to the technical field of ion exchange resin. The ion exchange resin capable of being used for dechlorination is prepared, the stability of the ion exchange resin in the dechlorination process is maintained through the added modified lignin, and groups with good affinity to chloride ions are introduced through concentrated sulfuric acid and amination treatment; finally, the dechlorination efficiency of the ion exchange resin is further improved through plasma treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ion exchange resins and relates to a method for preparing a chlorine-removing ion exchange resin. Background Art

[0002] The widespread use of chlorine-containing compounds such as HCl, NaCl, and MgCl2 in the industrial field increases the chloride ion content of wastewater. At the same time, the use of chlorine disinfection in water plants will also lead to an increase in the chlorine content in drinking water and domestic water. The accumulation of a large amount of chloride ions will cause soil salinization, and excessive chlorine intake by the human body will cause damage to the body.

[0003] At present, the main methods for removing chlorine from water at home and abroad are precipitation method, evaporation dechlorination technology, membrane separation technology, recrystallization method, and ultra-high lime aluminum method, but these methods have obvious shortcomings. Ion exchange resin has excellent ion exchange function and is also a carrier for completing ion exchange separation operations. Ion exchange resin is a polymer compound that contains a large number of active groups inside, which can exchange with ions in the solution. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a chlorine-removing ion exchange resin. The prepared ion exchange resin has good chlorine-removing performance.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a chloride-removing ion exchange resin comprises the following steps:

[0007] S1. Mix 65-75 parts of styrene, 10-15 parts of divinylbenzene, 3-5 parts of modified lignin and 0.2-0.4 parts of azobisisobutyronitrile by weight, heat to 75-90° C. and stir to obtain an oil phase mixture;

[0008] S2, 70-80 parts of deionized water, 5-10 parts of sodium chloride, 15-20 parts of polyvinyl alcohol, 5-8 parts of carboxyethyl cellulose and 2-4 parts of sodium lignin sulfonate are mixed, heated to 70-80° C. and stirred for 35-50 minutes to obtain an aqueous phase mixture;

[0009] S3. At room temperature, the oil phase mixture and the water phase mixture in a mass ratio of 1:(0.5-0.8) are mixed and ultrasonically treated for 1-2 hours, then the temperature is raised to 50-70°C, and the ultrasonic treatment is continued for 1-3 hours, and finally the temperature is raised to 80-90°C and ultrasonically treated for 3-4.5 hours. After the mixture is naturally cooled to room temperature, filtered, and washed with deionized water to obtain a mixture A;

[0010] S4, mixing the mixture A with N,N-dimethylformamide, adding 90-95% by mass of concentrated sulfuric acid, stirring for 1-2 hours, cooling naturally to room temperature, and washing the product to obtain a white ball;

[0011] S5, 10 to 25 parts of chloroform and 5 to 10 parts of white balls are mixed, and the mixture is swelled at room temperature for 3 hours, and then 15 to 30 parts of trioxane, 5 to 16 parts of trimethylsilyl chloride and 15 to 25 parts of anhydrous tin tetrachloride are added, and the mixture is stirred for 12 hours. After the stirring is completed, the mixed solution is filtered, and the obtained filter balls are washed with hydrochloric acid aqueous solution and deionized water in turn, and then 10 to 15 parts of triethylamine are added, and the stirring is continued for 10 to 13 hours to obtain an ion exchange resin matrix;

[0012] S6. Plasma-treating the ion exchange resin matrix with ammonia to obtain the chlorine-removing ion exchange resin.

[0013] As a preferred technical solution of the present invention, in step S1, the stirring time is 35 to 45 minutes and the rotation speed is 200 to 300 r / min.

[0014] As a preferred technical solution of the present invention, in step S1, the preparation process of the modified lignin is as follows:

[0015] A lauryl alcohol phosphate ethanol solution with a mass fraction of 10-15% is prepared, and then lignin and the lauryl alcohol phosphate ethanol solution are mixed in a mass ratio of (1-3):30, stirred at 50-75°C for 3-6 hours, centrifuged and washed after stirring, and dried at 85°C for 5-8 hours to obtain the modified lignin.

[0016] As a preferred technical solution of the present invention, in step S4, the specific process of washing is: washing the product with deionized water at 0°C, then eluting with a 5% by mass sodium hydroxide solution, acetone, and a 5% by mass hydrochloric acid solution for 5 to 8 minutes, and then washing with ionized water at 45 to 50°C until neutral.

[0017] As a preferred technical solution of the present invention, in step S4, the mass ratio of the mixture A, N,N-dimethylformamide and concentrated sulfuric acid is 1:4:10.

[0018] As a preferred technical solution of the present invention, in step S4, the rotation speed during stirring is 250-300 r / min and the temperature is 40-50°C.

[0019] As a preferred technical solution of the present invention, in step S5, the temperature during stirring is 30-60°C, and the rotation speed is 900r / min.

[0020] As a preferred technical solution of the present invention, in step S5, the mass fraction of the hydrochloric acid aqueous solution is 2-3%.

[0021] As a preferred technical solution of the present invention, in step S6, the power of the plasma treatment is 180 to 240 W, and the time is 100 to 150 s.

[0022] As a preferred technical solution of the present invention, in step S6, the mass ratio of the ion exchange resin matrix to the ammonia gas is (3-9):1.

[0023] The present invention uses styrene and divinylbenzene as the matrix to react under the action of initiator azobisisobutyronitrile to obtain an oil phase, and lignin is added to the oil phase. Lignin, as a natural macromolecular compound, contains multiple active functional groups in its molecular structure, such as hydroxyl, carboxyl, etc. Therefore, the structure in the lignin molecule helps to enhance the mechanical properties of the resin. By adding lignin, the viscosity of the ion exchange resin can be adjusted to make it easier to process and shape. Lignin has certain hydrophilicity and adsorption capacity, and can adsorb and remove some impurities and pollutants in water. Therefore, lignin can help the anti-pollution property of ion exchange resin in use and extend the service life of resin. At the same time, the addition of lignin can also reduce the adsorption of impurities in water by the resin in use, thereby improving the ion exchange efficiency and selectivity of the resin.

[0024] In the present invention, lignin is modified with lauryl alcohol phosphate, which is a surfactant that can significantly reduce the surface tension of the solution. Therefore, the modified lignin has lower surface energy. When the aqueous phase mixture is mixed with the oil phase mixture, the good dispersibility and stability of the modified lignin itself can effectively prevent the agglomeration and sedimentation of the resin particles, thereby improving the dispersibility and stability of the resin, which helps to ensure that the resin can be evenly distributed in the subsequent reaction and processing process, thereby making it more difficult for pollutants to adhere.

[0025] The molecular chain of carboxyethyl cellulose is relatively long and has a certain rigidity. During the preparation of ion exchange resin, it can form a cross-linked structure with the ion exchange resin matrix, thereby enhancing the mechanical strength of the resin. This strengthening effect enables the ion exchange resin to withstand greater pressure and stress during use, thus extending its service life.

[0026] The prepared white ball is then sulfonated with concentrated sulfuric acid to further improve the affinity of the ion exchange resin; and then chloromethylated and aminated in step S5 to obtain a quaternized ion exchange resin. When the ion exchange resin is used for dechlorination, the sulfonic acid group introduced by the sulfonation treatment can ionize H in water. +Ions and negatively charged sulfonate ions. When a solution containing chloride ions passes through the ion exchange resin, the chloride ions will exchange with the exchangeable anions on the resin and be adsorbed onto the material. At the same time, the quaternary ammonium group on the ion resin is a positively charged group that can attract and adsorb negatively charged chloride ions. When a solution containing chloride ions passes through the quaternary ammonium resin, the chloride ions will be adsorbed by the quaternary ammonium group in the resin and replace other anions originally in the resin. Therefore, the quaternary ammonium group directly adsorbs chloride ions as a fixed ion, while the sulfonic acid group indirectly adsorbs chloride ions through the exchangeable anions on it. These two mechanisms work together on the ion exchange resin, enabling it to effectively remove chloride ions from the solution.

[0027] In the process of plasma treatment of ion exchange resin with ammonia, ammonia molecules are excited into plasma state under the action of electric field, activating the chemical activity on the surface of resin, making it easier to exchange with chloride ions, thereby improving the efficiency of chlorine removal. In addition, plasma treatment can increase the surface roughness, provide more adsorption sites, facilitate the adsorption and exchange of chloride ions, and further improve the efficiency of chlorine removal. In addition, ammonia plasma treatment can form a protective film on the surface of resin, reduce the invasion of organic matter, microorganisms and other pollutants, which helps to keep the ion exchange resin clean and active, thereby extending its service life and improving the efficiency of chlorine removal.

[0028] Beneficial effects of the present invention:

[0029] The invention prepares an ion exchange resin that can be used for removing chlorine, and helps maintain the stability of the ion exchange resin in the process of removing chlorine by using modified lignin added therein, introduces groups with good affinity for chloride ions by concentrated sulfuric acid and amination treatment, and finally further improves the chlorine removal efficiency of the ion exchange resin by plasma treatment. DETAILED DESCRIPTION

[0030] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0031] Example 1

[0032] S1. Mix 65 parts of styrene, 10 parts of divinylbenzene, 3 parts of modified lignin and 0.2 parts of azobisisobutyronitrile by weight, heat to 75° C. and stir for 35 min at a speed of 200 r / min to obtain an oil phase mixture;

[0033] The preparation process of modified lignin is as follows:

[0034] A lauryl alcohol phosphate ethanol solution with a mass fraction of 10% is prepared, and then the lignin and the lauryl alcohol phosphate ethanol solution are mixed in a mass ratio of 1:30, stirred at 50° C. for 3 hours, centrifuged and washed after the stirring, and dried at 85° C. for 5 to 8 hours to obtain the modified lignin;

[0035] S2, 70 parts of deionized water, 5 parts of sodium chloride, 15 parts of polyvinyl alcohol, 5 parts of carboxyethyl cellulose and 2 parts of sodium lignin sulfonate were mixed, heated to 70° C. and stirred for 35 min to obtain an aqueous phase mixture;

[0036] S3. At room temperature, the oil phase mixture and the water phase mixture in a mass ratio of 1:0.5 were mixed and ultrasonically treated for 1 hour, then the temperature was raised to 50° C., and the ultrasonic treatment was continued for 1 hour, and finally the temperature was raised to 80° C. and ultrasonically treated for 3 hours. After the end, the mixture was naturally cooled to room temperature, filtered, and washed with deionized water to obtain a mixture A;

[0037] S4. Mix mixture A with N,N-dimethylformamide, add 90% concentrated sulfuric acid, stir for 1 hour, the speed of stirring is 250r / min, the temperature is 40°C, and then naturally cool to room temperature. Wash the product with 0°C deionized water, then rinse with 5% sodium hydroxide solution, acetone, and 5% hydrochloric acid solution for 5 minutes, and then wash with 45°C deionized water until neutral to prepare a white ball, wherein the mass ratio of mixture A, N,N-dimethylformamide and concentrated sulfuric acid is 1:4:10, wherein the speed of stirring is 250r / min, and the temperature is 40°C;

[0038] S5, 10 parts of chloroform and 5 parts of white balls were mixed, swelled at room temperature for 3 hours, and then 15 parts of trioxane, 5 parts of trimethylsilyl chloride and 15 parts of anhydrous tin tetrachloride were added, and stirred for 12 hours at a temperature of 30°C and a speed of 900 r / min. After the stirring was completed, the mixed solution was filtered, and the obtained filter balls were washed with a 2% hydrochloric acid aqueous solution and deionized water in turn, and then 10 parts of triethylamine were added, and stirring was continued for 10 hours to obtain an ion exchange resin matrix;

[0039] S6. Plasma-treating the ion exchange resin matrix with ammonia to obtain a chloride-removing ion exchange resin, wherein the power of the plasma treatment is 180 W, the time is 100 s, and the mass ratio of the ion exchange resin matrix to the ammonia is 3:1.

[0040] Example 2

[0041] S1. Mix 70 parts of styrene, 12 parts of divinylbenzene, 4 parts of modified lignin and 0.3 parts of azobisisobutyronitrile by weight, heat to 80° C. and stir for 39 minutes at a speed of 260 r / min to obtain an oil phase mixture;

[0042] The preparation process of modified lignin is as follows:

[0043] A lauryl alcohol phosphate ethanol solution with a mass fraction of 13% is prepared, and then the lignin and the lauryl alcohol phosphate ethanol solution are mixed in a mass ratio of 2:30, stirred at 59° C. for 4 hours, centrifuged and washed after the stirring, and dried at 85° C. for 6 hours to obtain the modified lignin;

[0044] S2, 75 parts of deionized water, 6 parts of sodium chloride, 18 parts of polyvinyl alcohol, 7 parts of carboxyethyl cellulose and 3 parts of sodium lignin sulfonate were mixed, heated to 75° C. and stirred for 40 minutes to obtain an aqueous phase mixture;

[0045] S3. At room temperature, the oil phase mixture and the water phase mixture in a mass ratio of 1:0.6 were mixed and ultrasonically treated for 1.5 hours, then the temperature was raised to 60° C., and the ultrasonic treatment was continued for 2 hours, and finally the temperature was raised to 85° C. and ultrasonically treated for 3.5 hours. After the mixture was naturally cooled to room temperature, filtered, and washed with deionized water to obtain a mixture A;

[0046] S4. Mix mixture A with N,N-dimethylformamide, add concentrated sulfuric acid with a mass fraction of 93%, stir for 1.5 hours, the speed of stirring is 270r / min, the temperature is 45°C, and then naturally cool to room temperature. Wash the product with deionized water at 0°C, and then rinse with 5% sodium hydroxide solution, acetone, and 5% hydrochloric acid solution for 6 minutes, and then wash with 47°C deionized water until neutral to prepare a white ball, wherein the mass ratio of mixture A, N,N-dimethylformamide and concentrated sulfuric acid is 1:4:10, wherein the speed of stirring is 280r / min, and the temperature is 45°C;

[0047] S5, 18 parts of chloroform and 7 parts of white balls were mixed, swelled at room temperature for 3 hours, and then 20 parts of trioxane, 11 parts of trimethylsilyl chloride and 19 parts of anhydrous tin tetrachloride were added, and stirred for 12 hours at a temperature of 50°C and a speed of 900 r / min. After the stirring was completed, the mixed solution was filtered, and the obtained filter balls were washed with a 2.5% mass fraction of hydrochloric acid aqueous solution and deionized water in turn, and then 13 parts of triethylamine were added, and stirring was continued for 12 hours to obtain an ion exchange resin matrix;

[0048] S6. Plasma-treating the ion exchange resin matrix with ammonia to obtain a chloride-removing ion exchange resin, wherein the power of the plasma treatment is 200 W, the time is 130 s, and the mass ratio of the ion exchange resin matrix to the ammonia is 5:1.

[0049] Example 3

[0050] S1. Mix 75 parts of styrene, 15 parts of divinylbenzene, 5 parts of modified lignin and 0.4 parts of azobisisobutyronitrile by weight, heat to 90° C. and stir for 45 min at a speed of 300 r / min to obtain an oil phase mixture;

[0051] The preparation process of modified lignin is as follows:

[0052] A lauryl alcohol phosphate ethanol solution with a mass fraction of 15% is prepared, and then the lignin and the lauryl alcohol phosphate ethanol solution are mixed in a mass ratio of 3:30, stirred at 75° C. for 6 hours, centrifuged and washed after the stirring, and dried at 85° C. for 8 hours to obtain the modified lignin;

[0053] S2, 80 parts of deionized water, 10 parts of sodium chloride, 20 parts of polyvinyl alcohol, 8 parts of carboxyethyl cellulose and 4 parts of sodium lignin sulfonate were mixed, heated to 80° C. and stirred for 50 min to obtain an aqueous phase mixture;

[0054] S3. At room temperature, the oil phase mixture and the water phase mixture in a mass ratio of 1:0.8 were mixed and ultrasonically treated for 2 h, then heated to 70°C and ultrasonically treated for 3 h, and finally heated to 90°C and ultrasonically treated for 4.5 h. After the mixture was naturally cooled to room temperature, filtered, and washed with deionized water to obtain a mixture A.

[0055] S4, mix the mixture A with N, N-dimethylformamide, add 95% concentrated sulfuric acid, stir for 2h, the speed of stirring is 300r / min, the temperature is 50°C, and then naturally cool to room temperature, wash the product with 0°C deionized water, and then rinse with 5% sodium hydroxide solution, acetone, and 5% hydrochloric acid solution for 8min, and then wash with 50°C deionized water until neutral to prepare a white ball, wherein the mass ratio of the mixture A, N, N-dimethylformamide and concentrated sulfuric acid is 1:4:10, the speed of stirring is 300r / min, and the temperature is 50°C;

[0056] S5, 25 parts of chloroform and 10 parts of white balls were mixed, swelled at room temperature for 3 hours, and then 30 parts of trioxane, 16 parts of trimethylsilyl chloride and 25 parts of anhydrous tin tetrachloride were added, and stirred for 12 hours at a temperature of 60°C and a speed of 900 r / min. After the stirring was completed, the mixed solution was filtered, and the obtained filter balls were washed with a 3% hydrochloric acid aqueous solution and deionized water in turn, and then 15 parts of triethylamine were added, and stirring was continued for 13 hours to obtain an ion exchange resin matrix;

[0057] S6. Plasma-treating the ion exchange resin matrix with ammonia to obtain a chloride-removing ion exchange resin, wherein the power of the plasma treatment is 240 W, the time is 150 s, and the mass ratio of the ion exchange resin matrix to the ammonia is 9:1.

[0058] Comparative Example 1

[0059] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the lignin is not modified, and the other operations are the same.

[0060] Comparative Example 2

[0061] The difference between Comparative Example 2 and Example 1 is that step S6 is not performed in Comparative Example 2, and the remaining operations are the same.

[0062] Performance Test:

[0063] The test water sample was taken from the alkaline effluent of a metal processing plant after the wastewater was precipitated with lime and coagulant. The raw water contained a large amount of Zn before precipitation. 2+ , Cl - , Ca 2+ And a small amount of Tl + The heavy metal ions in the water have been mostly removed after lime alkali precipitation, but the alkaline (pH=12.8) effluent still contains a large amount of chloride ions (about 1.60-1.70 mol / L). The test solution is taken for chlorine removal test.

[0064] Ion exchange resin pretreatment:

[0065] Soak the ion exchange resin in deionized water for 24 hours and rinse continuously until the eluate is clear; fill the resin into the ion exchange column, wash with 1mol / L HCl solution, control the flow rate at 15mL / min, time for 30min, rinse with deionized water until the effluent is neutral, then wash with 1mol / L NaOH solution, control the flow rate at 15mL / min, time for 30min, rinse with deionized water until the effluent is neutral.

[0066] Dynamic adsorption experiment:

[0067] The test solution was injected into the ion exchange column (10 mm in inner diameter, 200 mm in height) filled with the ion exchange resin prepared in the examples and comparative examples by a peristaltic pump. The solution flowed through the resin bed from top to bottom. The adsorbed solution was collected and the Cl content in the effluent at different times was determined. - concentration (mol / L), and the experimental temperature was controlled at 25 °C.

[0068] Cl in solution - The concentration was measured using a JF-WK-2000 microcoulometric analyzer (Jiangsu Jiangfen Electrical Analytical Instrument Co., Ltd.), and the test results are shown in the following table:

[0069] Group 5min 15min 25min Example 1 0.82 0.45 0.22 Example 2 0.89 0.52 0.31 Example 3 0.79 0.41 0.18 Comparative Example 1 0.99 0.69 0.50 Comparative Example 2 1.08 0.88 0.74

[0070] According to the above data, it can be seen that the ion exchange resin prepared in the present invention has good chlorine removal performance.

[0071] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a chloride-removing ion exchange resin, characterized in that: The following steps are involved: S1. Mix 65-75 parts of styrene, 10-15 parts of divinylbenzene, 3-5 parts of modified lignin and 0.2-0.4 parts of azobisisobutyronitrile by weight, heat to 75-90° C. and stir to obtain an oil phase mixture; S2, 70-80 parts of deionized water, 5-10 parts of sodium chloride, 15-20 parts of polyvinyl alcohol, 5-8 parts of carboxyethyl cellulose and 2-4 parts of sodium lignin sulfonate are mixed, heated to 70-80° C. and stirred for 35-50 minutes to obtain an aqueous phase mixture; S3. At room temperature, the oil phase mixture and the water phase mixture in a mass ratio of 1:(0.5-0.8) are mixed and ultrasonically treated for 1-2 hours, then the temperature is raised to 50-70°C, and the ultrasonic treatment is continued for 1-3 hours, and finally the temperature is raised to 80-90°C and ultrasonically treated for 3-4.5 hours. After the mixture is naturally cooled to room temperature, filtered, and washed with deionized water to obtain a mixture A; S4, mixing the mixture A with N,N-dimethylformamide, adding 90-95% by mass of concentrated sulfuric acid, stirring for 1-2 hours, cooling naturally to room temperature, and washing the product to obtain a white ball; S5, 10 to 25 parts of chloroform and 5 to 10 parts of white balls are mixed, and the mixture is swelled at room temperature for 3 hours, and then 15 to 30 parts of trioxane, 5 to 16 parts of trimethylsilyl chloride and 15 to 25 parts of anhydrous tin tetrachloride are added, and the mixture is stirred for 12 hours. After the stirring is completed, the mixed solution is filtered, and the obtained filter balls are washed with hydrochloric acid aqueous solution and deionized water in turn, and then 10 to 15 parts of triethylamine are added, and the stirring is continued for 10 to 13 hours to obtain an ion exchange resin matrix; S6. Plasma-treating the ion exchange resin matrix with ammonia to obtain the chlorine-removing ion exchange resin.

2. The method for preparing a chloride-removing ion exchange resin according to claim 1, wherein In step S1, the stirring time is 35 to 45 minutes, and the rotation speed is 200 to 300 r / min.

3. The method for preparing a chloride-removing ion exchange resin according to claim 1, characterized in that: In step S1, the preparation process of the modified lignin is as follows: A lauryl alcohol phosphate ethanol solution with a mass fraction of 10-15% is prepared, and then lignin and the lauryl alcohol phosphate ethanol solution are mixed in a mass ratio of (1-3):30, stirred at 50-75°C for 3-6 hours, centrifuged and washed after stirring, and dried at 85°C for 5-8 hours to obtain the modified lignin.

4. The method for preparing a chloride-removing ion exchange resin according to claim 1, wherein: In step S4, the specific process of washing is: washing the product with deionized water at 0°C, then eluting with 5% sodium hydroxide solution, acetone, and 5% hydrochloric acid solution in sequence for 5 to 8 minutes, and then washing with ionized water at 45 to 50°C until neutral.

5. The method for preparing a chloride-removing ion exchange resin according to claim 1, characterized in that: In step S4, the mass ratio of the mixture A, N,N-dimethylformamide and concentrated sulfuric acid is 1:4:

10.

6. The method for preparing a chloride-removing ion exchange resin according to claim 1, characterized in that: In step S4, the rotation speed during stirring is 250-300 r / min and the temperature is 40-50°C.

7. The method for preparing a chloride-removing ion exchange resin according to claim 1, characterized in that: In step S5, the stirring temperature is 30-60° C. and the rotation speed is 900 r / min.

8. The method for preparing a chloride-removing ion exchange resin according to claim 1, characterized in that: In step S5, the mass fraction of the hydrochloric acid aqueous solution is 2-3%.

9. The method for preparing a chloride-removing ion exchange resin according to claim 1, characterized in that: In step S6, the power of the plasma treatment is 180-240 W, and the time is 100-150 s.

10. The method for preparing a chloride-removing ion exchange resin according to claim 1, characterized in that: In step S6, the mass ratio of the ion exchange resin matrix to the ammonia gas is (3-9):1.

Citation Information

Cited By

  • Preparation method and application of high-entropy adsorption material

    CN122057485A